2019
DOI: 10.3390/sports7040080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 7-Week Hip Thrust Versus Back Squat Resistance Training on Performance in Adolescent Female Soccer Players

Abstract: Hip thrust (HT) is a loaded bridging exercise that requires more hip extension than a back squat (SQ) does, while in a back squat, triple flex extension occurs. Due to the specificity of each exercise, it is claimed that HT gains can be better transferred to actions where hip extension occurs. In addition, strength improvements during squatting can be transferred in a greater way to vertical plane movement, such as vertical jumping. However, its effects on the performance of female soccer players are unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
2
26
0
2
Order By: Relevance
“…A wide range of studies has been conducted to determine the applicability of a given exercise that leads to enhancement of specific athletic performance [ 22 , 23 , 24 , 25 ]. However, various resistance exercises are significantly related to performance of selected physical fitness tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of studies has been conducted to determine the applicability of a given exercise that leads to enhancement of specific athletic performance [ 22 , 23 , 24 , 25 ]. However, various resistance exercises are significantly related to performance of selected physical fitness tests.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Contreras et al [ 24 ] found that 6-week hip thrust training could be more beneficial in improving 10- and 20-m linear sprint times compared with front squat training, which may be superior in vertical jump height enhancement. In addition, González-García et al [ 25 ] revealed that strength improvement after 7-week hip thrust training showed greater improvements in 10- and 20-m sprint, as well as in COD test (90°) in comparison to back squat training [ 25 ]. It is possible that the hip thrust has a stronger transfer to sprint running, whereas the squat has more influence on vertical jump performance [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 121 studies [40-42, 64-66, 71-181] represented a total sample of 3419 football code athletes with a mean sample size of 12.0 ± 5.3 participants per training group. One hundred and ten studies were conducted in males, ten in females [97,113,127,128,139,140,147,151,173,181] and one in mixed populations [106]. The mean age of studies ranged from 10.1 to 26.8 years.…”
Section: Overviewmentioning
confidence: 99%
“…The high degree of heterogeneity reflects the diversity of the training effects presented. This is likely due to wide variation in the intervention characteristics, including training principles (e.g., frequency [73], duration [75,96], intensity [66,192], volume [111], other training completed), population characteristics (e.g., sex [106,193], chronological age [157], maturation [45], code [42], playing standard [40,97], playing position, baseline physical characteristics [182] and training experience [168]) and performance monitoring methodology (e.g., equipment [99,105], start position [194], environmental factors [37], testing frequency and re-test time point [195,196]). Therefore, although the supplementary tables (Electronic Supplementary Material Tables S1-S3) provide a summary of training methods for all 121 papers included in this meta-analysis, caution is warranted when interpreting the findings of this review and their implications for practice as the variation of the effect sizes demonstrates that training response is highly individualised.…”
Section: Summary Of Interventions To Develop Short-sprint Performancementioning
confidence: 99%
“…In this regard, soccer players predominately run throughout the game, while other high intensity activities like sprinting, jumping, kicking and changing direction are also important performance factors that require both maximal strength and anaerobic power of the neuromuscular system 1,2 . Given the importance of high intensity activities for soccer performance, training strategies that ensure their optimal development are continuously being investigated and also, in recent years is having a great importance in youth soccer players 3,4 .…”
Section: Introductionmentioning
confidence: 99%